The local interferon-corrective therapy in children with congenital cleft lip and palate, suffering from the recurrent respiratory infections - I. V. Nesterova (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
It is known that children with congenital cleft lip and palate are suffering from recurrent respiratory infections, which worsen the state of their health, and also complicate the results of reconstructive surgical treatment. The aim of the study was to detect defects of mucosal immunity in children with congenital cleft lip and palate, suffering from recurrent respiratory infections, and to create the program of local interferon corrective therapy with an assessment of its effectiveness. The studies included 56 children from the age of 1 to 3 years. Three groups of children were formed: group 1 – 26 children with congenital cleft lip and palate (antibiotic therapy); group 2 — 30 children with congenital cleft lip and palate (antibiotic therapy + local interferon therapy), group 3 — the control group. The clinical examination included a medical history, an assessment of the symptoms of recurrent episodes of acute respiratory infections and exacerbations of chronic infections. Microbiological studies were performed using standard methods. The status of local immunity was detected: the concentrations of secretory IgA, cytokines IL-17, IL-4, IL-6, IL-1β, IFNγ in the oral fluid were tested by ELISA. Results of the study established that in group 1 and group 2 clinical criteria of immunodeficiency with an infectious syndrome were revealed: repeated acute respiratory viral infections from 10 or more times a year, complicated by frequent exacerbations of chronic bacterial infection (up to 10 or more per year). Assessment of the state of local immunity in children with congenital cleft lip and palate revealed a lack of sIgA compared with the control group. Before treatment in group 2 oral fluid level of IL-17, IL-6 were statistically significant increase (p < 0.05); the results of the study also established increase in the level of IL-1β and a decrease in anti-inflammatory IL-4 and regulatory IFNγ relative to the control group (p > 0.05). After complex treatment with the inclusion of local interferon therapy in group 2 the appearance of sIgA, increase in the concentration of IL-4, IL-1β and a decrease IL-17 in oral fluid were observed (p > 0.05). The concentrations of IL-6, IFNγ did not change (p > 0.05). After treatment in group 2 there were a decrease in exacerbations of chronic upper respiratory tract infection and in frequency of acute respiratory viral infections compared with group 1 (p < 0.05). Positive clinical efficacy of local interferon therapy (the gel of recombinant IFNα2b in combination with oxidants — Viferon gel) in the process of staged rehabilitation of children with congenital cleft lip and palate has a protective clinical effect in reducing the frequency of acute respiratory viral infections, reducing the number of postoperative complications, reducing hospital stay, duration of antibacterial therapy and the number of exacerbations of chronic bacterial infection.